Qual é o impacto dos fungos entomopatogênicos sobre operárias forrageiras de Apis mellifera africanizada? - Boeira, Luana Michele (2019)
Apis mellifera bees (Hymenoptera: Apidae) are social insects that pollinate over 80% of plant species, in addition to producing honey, royal jelly, wax, propolis and apitoxin. However, these bees are disappearing and this is mainly related to the use of synthetic chemical insecticides, but little is known about the effect of entomopathogens used in the biological control of insect pests. Thus, the work aimed to evaluate the impact of entomopathogenic fungi, Beauveria bassiana and Metarhizium anisopliae on Africanized A. mellifera forage workers. For this, these fungi, at a concentration of 1x108 conidia.ml-1, were tested on A. mellifera forage workers. Two bioassays were carried out: 1) contact of A. mellifera with eucalyptus leaves immersed in each solution and 2) contact of sprayed glass surface with the treatments. For control, sterile distilled water containing Tween 80 [marca registrada] (0.01%) was used. After contact, the workers were transferred in a group of 20 individuals to PVC cages, covered with voile. Each treatment consisted of five repetitions (PVC cages) with 20 bees per repetition. These were stored in a climate-controlled room (27 ± 2ºC, 70 ± 10% U.R and 12 hour photophase). Worker survival / mortality were assessed from 1 to 240 hours. The bees that survived exposed to the fungi after 24 hours were submitted to flight analysis and resumed flight (fall), performed in a dark room. Ten bees were used per treatment for each test. The fungi B. bassiana and M. anisopliae in the concentration used do not reduced the surival of Africanized A. mellifera when in contact with Petri dishes. When tested in contact with eucalyptus leaves, only M. anisopliae fungus reduced bee survival. In the flight analysis and flight resumption, there was no significant difference between the workers from the control and those from the treatments with the fungus B. bassiana and M. anisopliae, proving that the use of these entomopathogens does not affect the flight of A. mellifera. In the flight analysis and flight resumption, there was no significant difference between the workers from the control and those from the treatments with the fungus B. bassiana and M. anisopliae, proving that the use of these entomopathogens does not affect the flight of A. mellifera. Only the fungus M. anisopliae negatively impacts the survival of A. mellifera forages when they came into contact with the product in eucalyptus leaves. Furthermore, according to the tests performed, the entomopathogenic fungi tested here do not negatively affect the forage workers of Africanized A. mellifera